Epidemiological characteristics of deceased of Influenza A in a tertiary care hospital at Ajmer, Rajasthan, India - Keswani, Mahesh; Meharda, Bharat; Gupta, Teena (International Journal of Research in Medical Sciences, 2019)
Background: Inﬂuenza A (H1N1) is a novel strain of the Inﬂuenza virus and is widely known as Swine Flu. It causes a respiratory illness and is very contagious. Symptoms of Inﬂuenza A (H1N1) are similar to those of the seasonal flu. First laboratory confirmed Influenza A (H1N1) case of India was reported from Hyderabad on 16th May 2009. Methods: The study was retrospective descriptive, record-based study and carried in deceased of Influenza A (H1N1) who were admitted in Jawaharlal Nehru Medical College and Hospital, Ajmer, Rajasthan, India from 01 January 2016 to 31 December 2018. Results: A total 1524 suspected cases were screened for Influenza A (H1N1) at JLN Medical College and Hospital, Ajmer during the period from 1st January 2016 to 31st December 2018. 294 cases were diagnosed as Influenza A (H1N1) positive and 44 died. Majority 25 (56.81%) were belonged to rural area and 30 (68.18%) females died as compare to 14 (31.18%) male. Conclusions: Incidence and mortality is common throughout the year but it more in winter months. Mortality is high in age group of 50 years and above, females and rural area. IEC activities should be throughout year.